1998
DOI: 10.1115/1.2841370
|View full text |Cite
|
Sign up to set email alerts
|

Computation of the Unsteady Transonic Flow in Harmonically Oscillating Turbine Cascades Taking Into Account Viscous Effects

Abstract: This paper presents the numerical results of a code for computing the unsteady transonic viscous flow in a two-dimensional cascade of harmonically oscillating blades. The flow field is calculated by a Navier–Stokes code, the basic features of which are the use of an upwind flux vector splitting scheme for the convective terms (Advection Upstream Splitting Method), an implicit time integration, and the implementation of a mixing length turbulence model. For the present investigations, two experimentally investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 29 publications
3
5
0
Order By: Relevance
“…It can be seen that our TKFMG code clearly shows that flutter is present for IBPA = −90 • . Also in the figure we have shown the results of Euler computations by Ji & Liu (1999), Gruber & Cartsens (1998). It can be observed that the trend is captured correctly, that is, regions of positive and negative aerodynamic damping given by computations are in agreement with those observed by experiments.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…It can be seen that our TKFMG code clearly shows that flutter is present for IBPA = −90 • . Also in the figure we have shown the results of Euler computations by Ji & Liu (1999), Gruber & Cartsens (1998). It can be observed that the trend is captured correctly, that is, regions of positive and negative aerodynamic damping given by computations are in agreement with those observed by experiments.…”
Section: Resultssupporting
confidence: 65%
“…In order to validate the method for aeroelastic applications as well as demonstrate the power of the method to deal with multiple oscillating bodies we have computed the unsteady flow for the 4th standard aeroelastic test case (Bolcs & Fransson 1986). Results from the present computations are also compared with other Euler computations (Gruber & Cartsens 1998;Ji & Liu 1999;Mani & Feng 2001). All of them predict the flutter using energy method (Carta 1967).…”
Section: Introductionmentioning
confidence: 91%
“…This method is applied by Grü ber and Carstens [8] on a cascade in forced vibration. They used structured meshes generated by elliptic grid generation.…”
Section: Introductionmentioning
confidence: 99%
“…The current trends in gas turbine design towards higher flow velocities and slender blades demand an accurate and detailed study of aeroelastic behavior of corn- pressor and turbine blades. The prediction of blade flutter is critical in turbomachinery design and development, and considerable experimental and computational efforts are currently being made to determine flutter boundaries in highly loaded cascades with transonic and supersonic inflow (Ayer and Verdon 1996, Griiber and Carstens 1996, FOrsching 1996, He 1996 It is, therefore, of great interest to develop numerical methods to accurately predict the unsteady aerodynamics of vibrating blades in cascade flows.…”
Section: Introductionmentioning
confidence: 99%